Eldorado in East Harlem - Rodriguez, Victor, 1944- (Arte Público Press, 2017)
Rene, all of seventeen and street-wise, is about to give up on the American Dream. Petty crimes, running drugs and ghetto adventures bring him and his gang closer to an illusory Eldorado. But soon, his daydreams of limousines, fine clothes and finer women turn into a living nightmare that threatens to end his life and the lives of those he loves. Eldorado in East Harlem is a page-turner of a novel, full of intrigue, surprise turns of plot and memorable characters.